COMPARATIVE ANALYSIS OF WORD FORMATION IN UZBEK AND ENGLISH FOOD VOCABULARY - Rasulova Yulduz Nurmuxammad kizi (International Journal of Literature and Language Studies, 2026)
This article presents a comparative analysis of word formation processes in Uzbek and English food vocabulary. Food-related lexicon is considered a culturally significant layer of language that reflects national identity, traditions, and lifestyle. The study investigates major morphological mechanisms such as compounding, affixation, borrowing, blending, clipping, and multiple word-formation processes in both languages. Special attention is given to typological differences between Uzbek as an agglutinative language and English as an analytic language, which significantly influence lexical formation strategies in culinary terminology. It also demonstrates how globalization and intercultural contact contribute to the enrichment and transformation of food vocabulary in both languages and the findings show that although Uzbek and English differ structurally in word-formation patterns, both systems actively reflect cultural experience and continuous lexical development. The study contributes to understanding the interaction between morphology and cultural linguistics in the domain of culinary vocabulary.